Experimental investigation of clay-straw building finishing layer under different drying conditions. Issue 2 (2nd April 2016) - Tamošiūnas, Tadas; Girkontas, Romas; Savickas, Andrius; Skuodis, Šarūnas; Mica, Lumir
Abstract: This manuscript represents investigation of six different clay mixtures under variable drying conditions, namely: bright yellow clay (typical for Lithuania), brown clay (Lithuania Sergėnai district), mixture of different clays, white Spanish clay, clay mass which is resistant for thermal coldness (with synthetic cardigan) and Lithuanian coarse clay with granite additives. Drying process was provided imitating natural drying process and fast drying in drying oven at 110 C°. The main idea of this study – imitate clay and clay-straw buildings drying process and to determine which of used clay types had smallest volumetric and linear deformations. Volumetric and linear deformations for clay-straw buildings is one of the most important factors evaluating cracking in this type of buildings. To reach this purpose six tiles of different clay types were used. Before drying stage water content, plasticity, and liquid limits index, respectively was determined for all types of clay. All clay tiles volumetric and linear deformations before and after drying process were measured with specialized view analysis program in order not to damage samples' form. According to the obtained results a clay type whith the smallest deforamations (volumetric and linear) was found. With the smallest volumetric and linear deformations clay-straw building is not only environmental friendly, sustainable and green, but it does not require a lot of maintenance during building life time.